IMPLEMENTASI ROBOT AVOIDER DALAM ROBOT LIEN FOLLOWER BERBASIS ROBOT EDUKASI ATmEGA32 - Ikhsan Ikhsan (Universitas Negeri Padang, 2016)
Robotic technology has just begun in the developed countries because of the development of computer technology which keep progress very rapidly, so that no doubt that robotic technology developed as well. Even the former robot is utilized in the field of industry only but it beginning to be developed for the field of housing, particularly for mobile robots. these Applications can use Avoider Robot (hurdles) and Line Follower Robot (liners). Each model of the robot is utilized in the completion of a particular case. a combination of Line Follower Robot and Avoider Robot Are the best qualified to support the performance of the line follower, in order to anticipate the obstacles from the used path of the line follower, so that the robot can avoid obstacles in its path to search for the next track (line). As a result the performance of line follower will not stop eventhough there is an obstacle on track